The Impact Diversity Management and High Involvement In High Performance Work Systems: A Field Study in Maysan Oil Company - Salah, Rasha (The Arab Journal of Administration, 2019)
The research aims to determine the nature of the correlation between diversity management and management of high involvement of human resources and high-performance work systems, and determine the impact of the moderator variable high involvement management of human resources on the relationship between diversity management and high-performance work systems. the research adopted the methodology was descriptive analytical, and the research determined a set of hypotheses as temporary anticipating answers for the problem of the research which were them tested by non-remarked statistical tools, research was conducted in the Maysan Oil Company on a sample of managers working in the central and executive departments totaling (85) manager. A questionnaire used as a tool in collecting data and information. The most important findings of the research is no correlation statistically significant differences found between diversity management and management of high involvement of human resources and high-performance work systems and introduce numeral from recommendations, including educating staff through training courses that demonstrate the relationship between diversity management and high involvement management of human resources and high performance work systems, and creating an organizational climate that recognizes the importance diversity management and high involvement management that changes the work systems of normal performance.